Swedish National study on Aging and Care in Kungsholmen (SNAC-K) COVID-19 Study - Fratiglioni, Laura; Beridze, Giorgi; Calderón-Larrañaga, Amaia (Karolinska Institutet, 2021)
Abstract

These data are collected from 1428 older adults aged 60 and above. The project is embedded in the ongoing Swedish National Study on Aging and Care in Kungsholmen (SNAC-K), a population-based study with regular health assessments since 2001. https://www.snac-k.se/

The SNAC-K COVID-19 study aims to: 1) Estimate the short-term collateral damage on older adults’ health during the first months of the COVID-19 outbreak; 2) Detect the long-term collateral repercussions on older adults health up to two years after the first outbreak; 3) Identify the risk profiles for such collateral damage by integrating the ongoing interview with additional SNAC-K data and registries.

The questionnaire explicitly focuses on the changes in the participants’ health and lives, i.e. collateral damage, since the onset of the pandemic (March 2020). Depending on the interview date, collateral damage is investigated in up to four different time periods: March 2020-June 2020, July 2020-September 2020, October 2020-December 2020, January 2021-present.

The questionnaire is administered via telephone interviews conducted by trained SNAC-K personnel. As of April 2021, the first interview has been conducted with 1428 participants and a follow-up interview has been conducted with 105 of them. 934 follow-up interviews are scheduled to be conducted between April 2021 and August 2021 and an additional 167 by the end of 2021.

Main Topics:

Topics covered in the SNAC-K COVID-19 study include:

• Demographics

• Living arrangement

• Health condition (general)

- Health status

- Care-seeking behaviors

- Vaccination history

• Health condition (COVID-19-related)

- COVID-19 symptoms

- COVID-19 testing & hospitalization

- Protective measures against COVID-19

- Sources of information on COVID-19

• Mental health & cognition

• Physical activity

• Psychosocial factors

• Formal & informal care

Standard measures used in SNAC-K COVID-19 study

• Three-item loneliness scale; Hughes, M. E., Waite, L. J., Hawkley, L. C., & Cacioppo, J. T. (2004). A Short Scale for Measuring Loneliness in Large Surveys: Results From Two Population-Based Studies. Research on Aging, 26(6), 655–672.

• Montgomery Åsberg Depression Rating Scale (MADRS); Montgomery, S. A., & Asberg, M. (1979). A New Depression Scale Designed to be Sensitive to Change. Br J Psychiatry, 134, 382–389.

Methodology




Data collection period

06/05/2020 – ongoing

Setting

Kungsholmen, Stockholm, Sweden

Study design

Cross-sectional (1428) + longitudinal (105 conducted, 1101 planned)

Analysis unit

Individual

Data collection mode

Telephone interview

Terms of Access

For further information on the SNAC-K COVID-19 study, please contact Amaia Calderón-Larrañaga (amaia.calderon.larranaga@ki.se (mailto:amaia.calderon.larranaga@ki.se) ). To apply for the data, please contact Maria Wahlberg (maria.wahlberg@ki.se (mailto:maria.wahlberg@ki.se) ). General conditions for withdrawal of data from SNAC-K can be found at https://www.snac-k.se/for-researchers/application-form/

Funding

This work was supported by the funders of the Swedish National study on Aging and Care (SNAC): the Ministry of Health and Social Affairs, Sweden; the participating county councils and municipalities; and the Swedish Research Council. A specific grant was obtained from the Swedish Research Council (2020-05931).

Ethical review

The study has been ethically approved by the Swedish Ethical Review Authority (dnr: 2020-02497)
Keywords: Epidemiology not elsewhere classified; Geriatrics and gerontology; Medical and Health Sciences; Medicin och hälsovetenskap; Epidemiology; Epidemiologi